Anatomic measurements of the posterior tympanum related to the round window vibroplasty in congenital aural atresia and stenosis patients. - Chen, Keguang; Yin, Dongming; Lyu, Huiying; Yang, Lin; Zhang, Tianyu; Dai, Peidong (Acta Oto-Laryngologica, 2016)
ConclusionsWith the aggravation of the external auditory canal malformation, the size of extra-niche fossa became smaller, providing concrete data and valuable information for the better design, selecting and safer implantation of the transducer in the area of round window niche. Three-dimensional measurements and assessments before surgery might be helpful for a safer surgical approach and implantation of a vibrant soundbridge. ObjectivesThe aim of this study was to investigate whether differences exist in the morphology of the posterior tympanum related to the round window vibroplasty among congenital aural atresia (CAA), congenital aural stenosis (CAS), and a normal control group, and to analyze its effect on the round window implantation of vibrant soundbridge. MethodsCT images of 10 normal subjects (20 ears), 27 CAS patients (30 ears), and 25 CAA patients (30 ears) were analyzed. The depth and the size of outside fossa of round window niche related to the round window vibroplasty (extra-niche fossa)and the distances between the center of round window niche and extra-niche fossa were calculated based on three-dimensional reconstruction using mimics software. Finally, the data were analyzed statistically. ResultsThe size of extra-niche fossa in the atresia group was smaller than in the stenosis group (p < 0.05); furthermore, the size of extra-niche fossa in the stenosis group was smaller than that of the control group (p < 0.05). There was no statistically significant difference of the depth of extra-niche fossa among different groups.